Dps promotes survival of nontypeable Haemophilus influenzae in biofilm communities in vitro and resistance to clearance in vivo - Pang, Bing; Hong, Wenzhou; Kock, Nancy D.; Swords, W E. (Frontiers in Cellular and Infection Microbiology, 2012)
Nontypeable Haemophilus influenzae (NTHi) is a common airway commensal and opportunistic pathogen that persists within surface-attached biofilm communities. In this study, we tested the hypothesis that bacterial stress-responses are activated within biofilms. Transcripts for several factors associated with bacterial resistance to environmental stress were increased in biofilm cultures as compared to planktonic cultures. Among these, a homolog of the DNA-binding protein from starved cells (dps) was chosen for further study. An isogenic NTHi 86-028NP dps mutant was generated and tested for resistance to environmental stress, revealing a significant survival defects in high-iron conditions, which was mediated by oxidative stress and was restored by genetic complementation. As expected, NTHi 86-028NP dps had a general stress-response defect, exhibiting decreased resistance to many types of environmental stress. While no differences were observed in density and structure of NTHi 86-028NP and NTHi 86-028NP dps biofilms, bacterial survival was decreased in NTHi 86-028NP dps biofilms as compared to the parental strain. The role of dps persistence in vivo was tested in animal infection studies. NTHi 86-028NP dps had decreased resistance to clearance after pulmonary infection of elastase-treated mice as compared to NTHi 86-028NP, whereas minimal differences were observed in clearance from mock-treated mice. Similarly, lower numbers of NTHi 86-028NP dps were recovered from middle-ear effusions and bullar homogenates in the chinchilla model for otitis media (OM). Therefore, we conclude that Dps promotes bacterial survival within NTHi biofilm communities both in vitro and in chronic infections in vivo.